Online Political Information, Public Opinion and Political Activism - A Descriptive Analysis - Chandrasekaran, Prabanand (Journal of Advanced Research in Journalism & Mass Communication, 2018)
The primary research interest is in the area of uses and users of online political information. Online Journalism aided by social networking sites, smartphones, fast mobile networks and visual communication apps are playing an increasingly important role in influencing the political opinion of the society. Unlike the conventional form of news dissemination by the traditional electronic media like the television or radio, the online news of information offers the users an option of immediate feedback or response to any news content thereby neutralizing the information from the source) and consolidating the information along with their own inputs. This feature of online journalism along with the technology, creative applications and extremely fast reach of news to a wide audience through mobile devices has added a new dimension to the political information available online. Such an increasing reach is making a demand for an in depth study of the users and uses of political information because misinformation and abuse of online resources can have serious consequences on our society. On the other hand, the heterogeneous nature of the users also plays an important role in their approach towards any information. The demographics and socioeconomic position of a user also might affect their news assimilation behaviour. This in turn shapes their reaction towards the news content which makes the dynamics of public opinion formation even more complex and thus makes the analysis of the users a must. Adding on to the issue is the affiliation of political parties to media houses which relay the news. This is significant because it might affect the credibility of the source in the minds of the users and also have a direct impact on their dependency of online political information on social networking sites and applications rather than the conventional media like television. Its impact on the user and public opinion also needs to be studied. Further, the form and style of political news online has changed from that of the traditional media. The content is presented in a more humorous, entertaining format along with catchy visuals and graphics, which might also be the reason for the deeper social penetration of such news content. Thus analyzing the reception and transmission of such information by the users is required. Investigating the Style, form, design of the online political news content, its impact on the users of various backgrounds and how it impacts the public opinion formation is the general goal of the research. How to cite this article: Chandrasekaran P. Online Political Information, Public Opinion and Political Activism - A Descriptive Analysis. J Adv Res Jour Mass Comm 2018; 5(4): 123-126.